Bacterial exudate effects on Cu2+ sorption by cells: Quantifying significant ternary interactions. (15th January 2015) - Swedlund, Peter J.; Moreau, Magali; Daughney, Christopher J.
Abstract: Bacteria exude a range of ligands which have diverse effects on trace metal geochemistry. This study evaluated the effect of ligands exuded by the bacterium Anoxybacillus flavithermus on the aqueous geochemistry of Cu 2+ . Proton and Cu 2+ binding by the exudate ligands were investigated via potentiometric titrations and polarographic studies, respectively. Despite the apparent complexity of the system the Cu 2+ –exudate interaction was well described by a single model reaction H2 L + Cu 2+ ⇔ LCu + 2H + . In a bacterial cell suspension the aqueous phase concentration of exudate ligands increased almost linearly with the age of the suspension. After 48 h the exuded ligands had roughly the same total binding capacity for Cu 2+ as the cells from which they were derived. To investigate the significance of the exudate on Cu 2+ uptake by the bacterial cells sorption experiments were conducted in ternary systems with bacterial cells and a range of concentrations of a well characterized exudate. The systems were modeled with the parameters derived from the binary Cu 2+ –cells and Cu 2+ –exudate experiments. Under conditions where the binary model parameters predicted that the exudate ligand would hold all of the Cu 2+ in solution there was unexpectedly appreciable Cu 2+ sorption by the cells. This indicated the presence of significant ternary interactions involving the Cu 2+, the cell surface sites and the exudate. The observations could be reasonably well described by adding to the binary model reactions a single reaction for a ternary complex with stoichiometry R2 CuLH 0 where R2 represents a cell wall binding site. The exudate ligands produced by bacterial cells had a significant effect on Cu 2+ partitioning between the solution and solid phases under the experimental conditions employed. However, the study shows that the strong complexes that exudate ligands can form with trace metals do not necessarily inhibit trace metal uptake by cells to the extent expected from first principles.